High-resolution identification and abundance profiling of cassava (Manihot esculenta Crantz) microRNAs - Khatabi, Behnam (BMC Genomics, 2016)
BACKGROUND: Small RNAs (sRNAs) are endogenous sRNAs that play regulatory roles in plant growth, development, and biotic and abiotic stress responses. In plants, one subset of sRNAs, microRNAs (miRNAs) exhibit tissue-differential expression and regulate gene expression mainly through direct cleavage of mRNA or indirectly via production of secondary phased siRNAs (phasiRNAs) that silence cognate target transcripts in trans. RESULTS: Here, we have identified cassava (Manihot esculenta Crantz) miRNAs using high resolution sequencing of sRNA libraries from leaf, stem, callus, male and female flower tissues. To analyze the data, we built a cassava genome database and, via sequence analysis and secondary structure prediction, 38 miRNAs not previously reported in cassava were identified. These new cassava miRNAs included two miRNAs not previously been reported in any plant species. The miRNAs exhibited tissue-differential accumulation as confirmed by quantitative RT-PCR and Northern blot analysis, largely reflecting levels observed in sequencing data. Some of the miRNAs identified were predicted to trigger production of secondary phased siRNAs (phasiRNAs) from 80 PHAS loci. CONCLUSIONS: Cassava is a woody perennial shrub, grown principally for its starch-rich storage roots, which are rich in calories. In this study, new miRNAs were identified and their expression was validated using qRT-PCR of RNA from five different tissues. The data obtained expand the list of annotated miRNAs and provide additional new resources for cassava improvement research. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-2391-1) contains supplementary material, which is available to authorized users.